EARLY ISLAMIZATION PATTERNS IN SOUTHEAST ASIA: THEIR CONTRIBUTION TO GLOBAL PEACE EFFORTS - Darmawijaya, Darmawijaya; Hasnidar, Hasnidar; Mahdiyyah, Anni Atiqah (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study is to explain the Early Islamization Pattern in Southeast Asia: Its Contribution to Global Peace Efforts. This study uses the Constructive Critical History Method. This historical science is a new historical science that focuses on problem solving and finding solutions to problems so that humans as historical actors can enjoy a better life in the present and in the future. This research finds that the “Pattern of Islamization of Trade and Civilizational Dialogue” is the “Early Pattern of Islamization in Southeast Asia.” This pattern took place from the end of the 7th century to the beginning of the 16th century. The agents of Islamization were Islamic traders or Islamic scholars who worked as traders. The weakness of this pattern is that it takes a long time. To achieve good results, this pattern requires the willingness and awareness of both the agents of Islamization and the indigenous population in undergoing the process of Islamization. This pattern does not have a negative impact on innocent Muslims and non-Muslims or those who live elsewhere. This pattern is carried out in a healthy and friendly manner that does not trigger cases of Islamophobia. Conclusion. This research contributes to overcoming the global impasse in addressing the crises, conflicts, wars, and disasters that emerged after COVID-19.